The effects of heparinized normal saline flushing and prophylactic enoxaparin on central venous catheter thrombosis in PICU hospitalized pediatric - Maryam Mohebbi; Effat Hosseinali Beigi; Rezvaneh Mohebbi; Maryam Ghodsi (Archives of Anesthesia and Critical Care, 2024)
Background: Central venous catheter (CVC) thrombosis is one of the most common complications of CVC that occurs in children and adults. Prevention of this blockage improves the treatment process and reduces treatment costs. Due to the lack of studies on preventive methods of CVC thrombosis, this study aimed to examine the effect of NS flushing heparinized and prophylactic dose of enoxaparin in prevention of CVC induced thrombosis in hospitalized patients in pediatric intensive care unit (PICU).